2010
DOI: 10.1152/japplphysiol.00442.2010
|View full text |Cite
|
Sign up to set email alerts
|

Activity level, apoptosis, and development of cachexia in ApcMin/+ mice

Abstract: Criteria for diagnosing cachexia in adults include unintentional loss in body weight, decreased strength, fatigue, anorexia, and low muscle mass. Cachexia is also associated with systemic inflammation, altered metabolism, and anemia. The Apc(Min/+) mouse is a model of cachexia directly related to intestinal tumor burden and subsequent chronic inflammation. These mice also demonstrate muscle weakness, fatigue, decreased volitional activity, and elevated circulating IL-6 levels. The purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 32 publications
4
97
0
Order By: Relevance
“…The role of Fis1 during wasting diseases is currently unknown, but Fis1 overexpression is proapoptotic (29,31,43). Apoptosis in skeletal muscle is commonly observed during cancer cachexia (10,22), and we have also seen apoptosis induced in cachectic Apc Min/ϩ mouse hindlimb muscle (7). In the Apc Min/ϩ mouse, muscle Fis1 expression may be inducing apoptosis providing an additional mechanism for linking muscle mass loss to mitochondrial content.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The role of Fis1 during wasting diseases is currently unknown, but Fis1 overexpression is proapoptotic (29,31,43). Apoptosis in skeletal muscle is commonly observed during cancer cachexia (10,22), and we have also seen apoptosis induced in cachectic Apc Min/ϩ mouse hindlimb muscle (7). In the Apc Min/ϩ mouse, muscle Fis1 expression may be inducing apoptosis providing an additional mechanism for linking muscle mass loss to mitochondrial content.…”
Section: Discussionmentioning
confidence: 57%
“…The inherent variability in cachexia development between mice is a strength of the Apc Min/ϩ mouse model, and Apc Min/ϩ mice cachexia symptom severity was assigned at the study's end as in previously published studies (6,7). Mice were classified as having mild, moderate, or severe cachexia based on their body mass, gastrocnemius muscle mass, and epididymal fat pad mass.…”
Section: Animals All Wt and Apcmentioning
confidence: 99%
“…Changes in both WBC and RBC counts are characteristic in colon cancer and have been show to occur in the Apc Min/ϩ mouse (8). We therefore also performed a complete blood count to determine the role of MCP-1 on these parameters in the Apc Min/ϩ mouse.…”
Section: Discussionmentioning
confidence: 99%
“…A complete blood count was performed as both white blood cell (WBC) and red blood cell (RBC) counts have been shown to be altered during progression of intestinal tumorigenesis in this mouse model (Table 1) (8). We found that overall WBC counts were increased in Apc Min/ϩ mice (13.6 m/mm 3 Ϯ 1.8) compared with wild-type (5.7 m/mm 3 Ϯ 0.6) (P Ͻ 0.05) and MCP-1 deficiency blunted this response (7.1 m/mm 3 Ϯ 0.9) (P Ͻ 0.05).…”
Section: Complete Blood Count and Plasma Il-6mentioning
confidence: 99%
“…The weight loss observed in some models is coincident with electrophysiological muscle fatigue (Aulino et al, 2010; Baltgalvis et al, 2010; Murphy et al, 2012; Norden et al, 2014), reduced locomotor activity (Lamkin et al, 2011; Murphy et al, 2012; Xiu et al, 2010), and reduced voluntary wheel running (Baltgalvis et al, 2010; Wood et al, 2006). Reduced locomotor activity may reflect fatigue or physical limitations due to the tumor location and/or changes in areas of the CNS that regulate movement (Dantzer et al, 2012).…”
Section: Rodent Models Of Cancermentioning
confidence: 99%